PEMANFAATAN UNSUR NITROGEN LIMBAH BUDIDAYA IKAN LELE SEBAGAI PUPUK CAIR ORGANIK - kurnia sada harahap (Institut Pendidikan Tapanuli Selatan, 2019)
Inorganic chemical fertilizer and pesticides had a negative impact who have lost , not only for humans but also with the environment and organism and have a bad impact of soil fertility negative because of the influence of chemical molecule who break the regeneration of humus .The price of fertilizer or manure inorganic chemistry that the higher and the existence of the government policy to reduce fertilizer subsidy so efforts are needed to the use of fertilizer is better and more cheap namely organic fertilizers. The general objectives of the study analyzed / knew the amount of nitrogen element on waste the cultivation of fish catfish , know the number of doses of liquid fertilizer / organic waste the cultivation of fish catfish in fertilizing plant with memanfaatankan nitrogenous element there are the cultivation of fish catfish on waste as a fertilizer looking for organic. The manufacture of fertilizers organic but the ocean is liquid have been carried out with the phases of as follows the local authority by preparing a bucket and the installation of an airasi , take the water waste the cultivation of fish lele and incorporated into embar , added that bekteri parser ( probiotics ) and molasses , a euml ration of the face that is through incorporation , the fermentation of the waste water the cultivation of fish will be let off because catfish and was conducted of the observation of nitrates and nitrites in order to understand the the moisture content of the element of nitrogen. The waste water from the cultivation of fish catfish elements convey a natural nitrogen ( n ) that can be used as a fertilizer liquid organic .The provision of probiotics and molasses flow in national monument catfish of the type of waste you think the cultivation of fish is able to improve the moisture content of nitrogen .That you may be old the process of fermentation waste water freshwater catfish of so the moisture content of nitrogen ( n ) will rise up significantly .The number of probiotics and molasses from the comparison 1: 1 and 1: 2 able to increase the number of nitrogen ( n )